Implementasi Model Pembelajaran Two Stay Two Stray dalam Meningkatkan Prestasi Belajar Biologi Siswa Kelas XB SMA Plus Al-Hasan Panti Jember. - Siti Roudlotul Hikamah (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2014)
Learning models Two Stay Two Stray is the one of a wide range of cooperative learning that expected to provide a new atmosphere for students to improve student achievement and enhance learning activities in the biological activity in particular. The purpose of this study is to analyze student achievement XB class sub concept of environmental pollution in SMA Plus AL-HASAN with the implementation of Two Stay Two Stray learning model and analyze the activities of students during the learning model biology lesson with Two Stay Two Stray sub concept of environmental pollution. The research was conducted in SMA Plus AL-HASAN Panti - Jember on the XB-class standards of competence and basic competences 4 and 4.2. Respondents who studied a total of 39 people. The method that used is Classroom Action Research. Analysys data using Description of Quantitative and One Sample T-test with SPSS 11.5 program. The results obtained in mind that the application of Learning Model Two Stay Two Stray can improve student achievement school class XB SMA Plus AL-HASAN is characterized by the difference between treatments is very significant (P = 0.00, P <0.05). As for the learning activities of students in biology has increased following the good.Key words: learning models, Two Stay Two Stray, school performance, student activities